Gastrointestinal parasites in pigs: prevalence and diagnosis - Edmund, C. C. M. (Veterinary Association Malaysia, 2005)
The prevalence of gastrointestinal parasites in pigs in Shah Alam abattoir, Selangor was studied. A total of 120 faecal samples were collected. Each faecal sample was examined by direct smear (DS), simple floatation (SF) and formal-ether sedimentation (FES). The results revealed the presence of Balantidium coli (53.3%), Trichuris suis (17.5%), Ascaris suum (15.8%), coccidia (11.6%), strongyles (8.3%), Entamoeba suis (2.5%) and Echinostoma malayanum (1.7%). The detection rates for B. coli and E. malayanum were highest with FES. The detection rates for coccidia, Trichuris suis and strongyles were highest with SF. The detection rates for Ascaris suis and Entamoeba suis were the same with FES and SF. Generally DS had the lowest detection rate compared to FES and SF. The agreement between FES and SF was the highest when compared to SF and DS; FES and DS. It is concluded that the SF remains the method of choice for the detection of gastrointestinal parasites in pigs.